If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -9m + -2m = 4m + 56 Combine like terms: -9m + -2m = -11m 20 + -11m = 4m + 56 Reorder the terms: 20 + -11m = 56 + 4m Solving 20 + -11m = 56 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 20 + -11m + -4m = 56 + 4m + -4m Combine like terms: -11m + -4m = -15m 20 + -15m = 56 + 4m + -4m Combine like terms: 4m + -4m = 0 20 + -15m = 56 + 0 20 + -15m = 56 Add '-20' to each side of the equation. 20 + -20 + -15m = 56 + -20 Combine like terms: 20 + -20 = 0 0 + -15m = 56 + -20 -15m = 56 + -20 Combine like terms: 56 + -20 = 36 -15m = 36 Divide each side by '-15'. m = -2.4 Simplifying m = -2.4
| 4x^2+1=-5 | | x+x+x+18-5=303 | | -x+5=1/2x-1 | | 6y=23-7 | | -5-5x=-10 | | x+18-5=303 | | 97=16+3q | | 4x^2+1=5 | | 2(y-3)=y+5 | | -3x+2x-4=-10 | | (3v+8)(1-v)=0 | | 9-10x=-4(2x-7)+3(5x-7) | | q+-8=3 | | f(x)=3x^2-12x | | (1[3v+8]1)(1[1-v]1)=0 | | 5y-2-8y=18 | | 3n-9=-18 | | x+2yi=6 | | 22-2a=12 | | y=(2x-4)(3x-2) | | 4y^2+13x+3=0 | | (g+10)=(2g-5) | | 4(x+3)(x-5)=0 | | -5x^2+7x=6 | | 9c+3=93 | | 2.5q-4.2-3.4q=-1.9q-1.6 | | 8x+13y=179 | | 27=-9h+3h | | (-8ab)(a^2b^5)= | | t+12.5=-5.5 | | 1.6+2.142x=.18x-2.15 | | 10x+70=690 |